Productive parameters and carcass yield of rabbits supplemented with Leucaena leucocephala (Lam.) de Wit., and Guazima ulmifolia Lam. foliage: Producción de conejos (Agro Productividad, 2021)
Objective: To determine the effect of the addition of Leucaena leucocephala andGuazima ulmifolia foliage on the production parameters and carcass yield of NewZealand rabbits.Desing/methodology/approach: 30 rabbits (15 females and 15 males) of the NewZealand breed were used, distributed in three treatments (five females and five males),which consisted in feeding 200 g of concentrated food per day + 100 g of fresh L.leucocephala or G. ulmifolia foliage, and a control group with no supplementation.Results: The total voluntary intake was not affected by the treatments or gender of therabbits; an average value of 158.9 g day -1 was recorded. Weight gain was 27.2 g day -1on average. The average slaughter weight of the rabbits was 2523 g. The carcassweight was 1,297 g and the average carcass yield was 51.6%. The dissectable fat 2content was lower in rabbits on supplements (F = 6.70, P = 0.001) with values of 1.6, 1.8and 2.11% with fresh foliage of G. ulmifolia, L. leucocephala and withoutsupplementation, this variable was not affected by gender. The viscera proportion wason average 24.3%. The average meat: bone ratio was 5.6.Limitations on study/implications: It was not possible to carry out bromatologicalanalyzes of the foliages or their digestibility.Fingings/conclusions: Supplementation of rabbits with foliage of G. ulmifolia and L.leucocephala decreases the proportion of dissectable fat and did not affect theproduction parameters and carcass yield.